Lymphatic Vasculature in Energy Homeostasis and Obesity - Ho, Yen-Chun; Srinivasan, R. Sathish (Frontiers in Physiology, 2020)
Obesity is a leading cause of cardiovascular diseases and cancer. Body mass is regulated by the balance between energy uptake and energy expenditure. The etiology of obesity is determined by multiple factors including genetics, nutrient absorption and inflammation. Lymphatic vasculature is starting to be appreciated as a critical modulator of metabolism and obesity. The primary function of lymphatic vasculature is to maintain interstitial fluid homeostasis. Lymphatic vessels absorb fluids that extravasate from blood vessels and return them to blood circulation. In addition, lymphatic vessels absorb digested lipids from the intestine and regulate inflammation. Hence, lymphatic vessels could be an exciting target for treating obesity. In this article we will review our current understanding regarding the relationship between lymphatic vasculature and obesity, and highlight some open questions.